2022
DOI: 10.1002/stc.3079
|View full text |Cite
|
Sign up to set email alerts
|

Multiclass damage detection in concrete structures using a transfer learning‐based generative adversarial networks

Abstract: A large amount of the world's existing infrastructure is reaching the end of its service life, requiring intervention in the form of structural rehabilitation or replacement. A critical aspect of such asset management is the condition assessment of these structures to evaluate their existing health and dictate the scheduling and extent of required rehabilitation. It has been demonstrated that human-based manual inspections face logistical constraints and are expensive, time extensive, and subjective, depending… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…In the civil SHM literature, there are also others [ (Wang et al, 2019;Rastin et al, 2021;Yuan et al, 2021;Yang et al, 2022;Huang et al, 2020;Sathya et al, 2020;Sun et al, 2022;Dunphy et al, 2022)] (a total of 10 studies) who are observed that do not fit a category and address different problems. It is observed that the subject of "damage detection after increased resolution" has one study (Sathya et al, 2020) in the literature where the researchers use SRGAN to increase the resolution of the images to improve the performance of the damage classifier.…”
Section: Frontiers In Built Environmentmentioning
confidence: 99%
See 2 more Smart Citations
“…In the civil SHM literature, there are also others [ (Wang et al, 2019;Rastin et al, 2021;Yuan et al, 2021;Yang et al, 2022;Huang et al, 2020;Sathya et al, 2020;Sun et al, 2022;Dunphy et al, 2022)] (a total of 10 studies) who are observed that do not fit a category and address different problems. It is observed that the subject of "damage detection after increased resolution" has one study (Sathya et al, 2020) in the literature where the researchers use SRGAN to increase the resolution of the images to improve the performance of the damage classifier.…”
Section: Frontiers In Built Environmentmentioning
confidence: 99%
“…There is one study on the topic of "track irregularity estimation" on acceleration data (Yuan et al, 2021), one study on the topic of "damage identification" via acceleration data (Rastin et al, 2021), and three studies on the topic of "Annotation reduction via transfer learning" [ (Huang et al, 2020); Dunphy et al, 2022)] which aim to reduce the need of annotating data through transfer-learning are other instances of GAN applications in civil SHM.…”
Section: Frontiers In Built Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, multiple detections are essential to comprehend the actual scenario of damage condition of any structure. Even though some studies have worked with different types of damages [26,27], the image dataset is minimal for some cases, i.e., spalling, and rebar exposure. Moreover, most prior research lacks multiple CNN model analyses and detailed sensitivity analyses of hyper-parameters.…”
Section: Reserarch Objective and Contributionmentioning
confidence: 99%
“…Wang et al [28] utilized TL to determine damage types caused by the repeated bearing of mechanical operations and natural factors, enhancing the service life of a pressure container. Dunphy et al [29] applied TL and generative adversarial networks for multiclass damage detection within infrastructures. Chamangard et al [30] reported successful TL application in accurately diagnosing invisible damage within complex structures.…”
Section: Introductionmentioning
confidence: 99%